Asālibu al Ikhtibārāti fi al Madārisi al Dīniyyati bi Manṭiqati Pitigala fī Syarqi Sri Lanka (Dirāsatun Taḥlīliyyatun Waṣfiyyatun) - Rasheed, A. Abdul; Mohideen, H.L.Meera (Al-Uslub: Journal of Arabic Linguistic and Literature, 2021)
Testing is an important step in the learning and teaching process. It has an important role in evaluating the teacher's duty and facilitating learners to express their opinions during and after the learning and teaching process. Arabic colleges in Sri Lanka are private institutes that do not have a proper curriculum, each following separate curricula. So, the methods of testing differ according to the curricula of these schools. It should be given attention in the field of research in order to achieve educational objectives. This study seeks to identify a best test and its importance in the field of teaching Arabic to non-native speakers and to identify Arabic colleges in Batticaloa District, East Sri Lanka, and also describes the evaluation methods used at Jamiathul Falah Arabic College in Kattankudy as a sample. The two researchers used the descriptive approach and the analytical method to complete this study and to reach the required results. They also carried out extrapolation and the library method to collect academic and cultural information, and used the interview as a tool for collecting information. The study found that schools in Batticaloa district conduct the weekly and the quarterly tests and follow different and varied forms in setting question papers. Jamiathul Falah Arabic College is distinguished by its tests, as it follows appropriate methods and good curricula according to students and their educational levels, the individual differences and concerning best methods in all its tests, such as objective type and others